KNOWLEDGE AND VALUES OF LOCAL WISDOM OF THE NAGARI SUNGAI BULUH COMMUNITY IN PADANG PARIAMAN REGENCY IN DISASTER MITIGATION (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2023)
This study aims to determine the level of knowledge and identify the values and of local wisdom of the people of Padang Pariaman Regency in disaster mitigation. This type of research is survey research method with a qualitative. The population in this study is the Nagari Sungai Buluh community. Data collection techniques using questionnaires and interviews. Descriptive qualitative data analysis using frequency and percentage tables. The results of this study indicate that the level of knowledge of the people of Padang Pariaman Regency in disaster mitigation shows high knowledge and many values and practices of local wisdom that exist in the midst of the community who teach about disaster mitigation.